Toulmin Argument Patterns in Asian EFL Learners' Essays: Gender and Topic-Based Comparison - Indarti, Dwi (Universitas Pendidikan Mandalika, 2025)
This study explores Toulmin Argument Patterns (TAP) in argumentative essays by Asian EFL learners, focusing on gender and topic-based comparison. Using an adapted Toulmin model, it analyses argument components, claims, data, counter-arguments, and rebuttals, from the ICNALE corpus on topics